The Utility of Chest Imaging for Surveillance of Atypical Lipomatous Tumors. (11th October 2021) - Lazarides, Alexander L.; Ferlauto, Harrison R.; Burke, Zachary D. C.; Griffin, Anthony M.; Leckey, Bruce D.; Bernthal, Nicholas M.; Wunder, Jay S.; Ferguson, Peter C.; Visgauss, Julia D.; Brigman, Brian E.; Eward, William C.
Abstract : Synopsis . For ALTs, the utility of chest surveillance has not been well defined. This study suggests that chest imaging does not have a significant role in the surveillance of ALTs. Advanced local imaging and more intensive chest surveillance may be considered in cases of local recurrence. Background . Unlike other soft tissue sarcomas, atypical lipomatous tumors (ALTs) are thought to have a low propensity for metastasis. Despite this, a standard of care for pulmonary metastasis (PM) surveillance has not been established. This study aimed to evaluate the utility of chest imaging for PM surveillance following ALT excision. Methods . This was a multi-institution, retrospective review of all patients with primary ALTs of the extremities or superficial torso who underwent excision between 2006 and 2018. Minimum follow-up was two years. Long-term survival was evaluated using the Kaplan–Meier method. Results . 190 patients with ALT were included. Average age was 61.7 years and average follow-up was 58.6 months (24 to 180 months). MDM2 testing was positive in 88 patients (46.3%), and 102 (53.7%) did not receive MDM2 testing. 188 patients (98.9%) had marginal excision, and 127 (66.8%) had marginal or positive margins. Patients received an average of 0.9 CT scans and 1.3 chest radiographs over the surveillance period. 10-year metastasis-free survival was 100%, with no documented deaths from disease. Conclusions . This study suggests that chest imaging does not have a significant role in PM surveillance following ALT excision, but advanced local imaging and chest surveillance may be considered in cases of local recurrence or concern for dedifferentiation.